Effective method for the purification of the lipid components in chilli powder / Ibtisam Abd Wahab - Abd Wahab, Ibtisam (Universiti Teknologi MARA Cawangan Pahang, 2020)
Local chilli pepper (Capsicum) plants contain rich resources of ingredients which can be used in the development and synthesis of pharmaceutical products. Therefore, phytochemical analysis is required in order to extract and identify the important bioactive compounds, derived from the chilli, to be used as therapeutic elements for humans. In this study, the compositions of Capsicum species were investigated by using chromatographic and spectroscopic methods. Following the organic extraction, the sample was investigated via analytical thin layer chromatography. It is believed that this technique is effective in separating the extract for preliminary qualitative analysis. The nonpolar constituents were later isolated by using preparative scale. From the findings, lipid fraction could be identified. In summary, proton Nuclear Magnetic Resonance (NMR) spectroscopy could provide useful spectral data on the composition of the triacylglycerol of this spice.